The diagnosis way towards rehabilitation: feelings and support network of women experiencing cancer and mastectomy / O caminho do diagnóstico à reabilitação: os sentimentos e rede de apoio das mulheres que vivenciam o câncer e a mastectomia - Ângela Urio; Jeane Barros de Souza; Maraísa Manorov; Rozana Bellaver Soares (Universidade Federal do Estado do Rio de Janeiro, 2019)
Objective: The study's goal has been to know the feelings of women before the diagnosis of breast cancer and the need for mastectomy, identifying their support network in coping with the disease. Methods: It is a descriptive-exploratory study with a qualitative approach. A script with semi-structured questions was used for data collection and the data arrangement occurred through content analysis. Results: There were ten mastectomized women residing in Chapecó city, Santa Catarina State. The feelings about the cancer diagnosis ranged from despair and fear of death, up to the effort to overcome it. Regarding the feelings associated with experiencing the mastectomy, the shock came out, also negative thinking, understanding of the need to removing the breast and resilience. The support networks were described mainly as family, friends, and faith. Conclusion: When facing the diagnosis, women come up with many uncertainties; therefore, it is necessary stimulating health professionals to support women in the disease coping process.